Making judgments based on reported observations of trainee performance: a scoping review in Health Professions Education - Blanchette, Patricia; Poitras, Marie-Eve; Lefebvre, Audrey-Ann; St-Onge, Christina (Canadian Medical Education Journal, 2024)
Background: Educators now use reported observations when assessing trainees’ performance. Unfortunately, they have little information about how to design and implement assessments based on reported observations. Objective: The purpose of this scoping review was to map the literature on the use of reported observations in judging health professions education (HPE) trainees' performances. Methods: Arksey and O'Malley’s (2005) method was used with four databases (sources: ERIC, CINAHL, MEDLINE, PsycINFO). Eligibility criteria for articles were: documents in English or French, including primary data, and initial or professional training; (2) training in an HPE program; (3) workplace-based assessment; and (4) assessment based on reported observations. The inclusion/exclusion, and data extraction steps were performed (agreement rate > 90%). We developed a data extraction grid to chart the data. Descriptive analyses were used to summarize quantitative data, and the authors conducted thematic analysis for qualitative data. Results: Based on 36 papers and 13 consultations, the team identified six steps characterizing trainee performance assessment based on reported observations in HPE: (1) making first contact, (2) observing and documenting the trainee performance, (3) collecting and completing assessment data, (4) aggregating assessment data, (5) inferring the level of competence, and (6) documenting and communicating the decision to the stakeholders. Discussion: The design and implementation of assessment based on reported observations is a first step towards a quality implementation by guiding educators and administrators responsible for graduating competent professionals. Future research might focus on understanding the context beyond assessor cognition to ensure the quality of meta-assessors’ decisions.